Kecanduan Game: Tingkat Emosi pada Mahasiswa Remaja - Imam Ekoputranto Sriadiatmaji; Arief Budi Yulianti; Ajeng Kartika Sari (Bandung Conference Series: Medical Science, 2023)
Abstract. Game online are games that are played at the same time even though they are not played in the same place. Faculty of Medicine students are students who are currently studying medical studies. Faculty of Medicine students are known for their busy schedules and many assignments, so they play game online to overcome boredom. Game online addiction can be understood as an excessive attitude towards the use of digital tools to play game online, makes players unable to control attitudes and emotions caused by excessive attitudes, and can have an impact on social behavior problems, especially at the emotional level. The purpose of this study was to analyze the relationship between game online addiction and emotional levels in medical students at the Islamic University of Bandung. In the results of this study it was revealed that of the 114 students of the Faculty of Medicine at the Islamic University of Bandung, the dominant ones were not addicted to game online (81.6%) and had good emotions in playing game online (66.7%). From the results of this study it was found that the value of P = 0.490 which stated that there was no relationship between game online addiction and emotional levels in students of the Faculty of Medicine, Islamic University of Bandung. This is based on the existence of several things that can affect emotional levels such as student achievement and also good emotional intelligence. Abstrak. Game online adalah game yang dimainkan dalam waktu yang bersamaan walaupun tidak dimainkan di tempat yang sama. Mahasiswa Fakultas Kedokteran merupakan mahasiswa yang sedang belajar dalam studi kedokteran. Mahasiswa Fakultas Kedokteran dikenal dengan jadwal yang padat dan juga tugas yang banyak, sehingga mereka bermain game online untuk mengatasi jenuh. Kecanduan game online dapat dipahami sebagai sikap berlebihan terhadap penggunaan alat digital untuk bermain game online, membuat pemain tidak dapat mengontrol sikap dan emosi yang disebabkan oleh sikap berlebihan, dan dapat berdampak pada masalah perilaku sosial terutama pada tingkat emosional. Tujuan dari penelitian ini adalah untuk menganalisa hubungan kecanduan game online terhadap tingkat emosi pada mahasiswa fakultas kedokteran Universitas Islam Bandung. Pada hasil penelitian ini terungkap bahwa dari 114 orang mahasiswa Fakultas Kedokteran Universitas Islam Bandung dominan tidak mengalami kecanduan game online (81,6 %) dan memiliki emosi baik dalam bermain game online (66,7%). Dari hasil penelitian tersebut didapatkan bahwa nilai P = 0,490 yang menyatakan bahwa tidak terdapat adanya hubungan antara kecanduan game online terhadap tingkat emosi pada mahasiswa Fakultas Kedokteran Universitas Islam Bandung. Hal tersebut didasarkan pada adanya beberapa hal yang dapat mempengaruhi tingkat emosi seperti prestasi belajar mahasiswa dan juga kecerdasan emosional yang bagus.